Partitioning for Enhanced Statistical Power and Noise Reduction: Comparing One-Way and Repeated Measures Analysis of Variance (ANOVA) - Strale, Frederick (Curēus (Palo Alto, CA), 2024)
Using simulated data with duplicate observational data points, this research aims to highlight the notable efficiency of repeated measures analysis of variance (ANOVA) compared to one-way ANOVA as a more powerful statistical model. One of the principal advantages of repeated measures ANOVA is its design, in which each subject acts as their own control. This methodology allows for the statistical mitigation of individual differences among subjects, thereby reducing extraneous variability (noise) that can obscure the effects of the experimental conditions under investigation. By employing identical simulated column values within this analysis, we observe that the F-statistic generated by the repeated measures ANOVA tends to be larger than that derived from the one-way ANOVA. A distinguishing feature of repeated measures ANOVA is its incorporation of an additional dimension of within-subject variation in its partitioning procedure. This acknowledges that measurements taken from the same subject are inherently correlated. This correlation introduces a separate source of partitioned variation, distinct from that attributable to between-subject differences. The term SS encapsulates the residual variation that remains after accounting for both group differences and individual subject discrepancies. By explicitly recognizing the interrelatedness of measurements collected from the same subjects, repeated measures ANOVA effectively reduces the residual error variation contributing to the denominator in calculating the F-statistic. This reduction in error variation (noise) results in a more sensitive statistical test than one-way ANOVA, thus enhancing the power of the analysis. Consequently, the ability of repeated measures ANOVA to account for the correlated nature of repeated observations not only yields a more robust estimation of the treatment effects but also fortifies the statistical conclusions drawn from the data.